Green Entrepreneurial Orientation and Sustainable Performance of SMEs in Indonesia and Malaysia - Sulastri Sulastri; Ratih Hurriyati; Heny Hendrayati; Noor Faizah Mohd Lajin; Sharifah Zannierah Syed Marzuki (Universitas Mercu Buana, 2026)
Objectives: This study investigates Green Entrepreneurial Orientation (GEO) as a key driver of Green Innovation (GI) in Small and Medium Enterprises (SMEs) in Indonesia and Malaysia. It examines how environmentally oriented entrepreneurial strategies encourage the adoption of green technologies, sustainable processes, and eco-friendly products. By integrating GEO into their operations, SMEs can enhance innovation, strengthen competitive advantage, and achieve sustainable performance while reducing environmental impacts.Methodology: A quantitative research approach was employed using a cross-sectional survey of 200 SME owners and managers in Indonesia and Malaysia. Data were collected via structured questionnaires and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM), including comprehensive assessments of the measurement model, structural model, and mediation effects.Finding: The results indicate that Green Entrepreneurial Orientation has a significant positive effect on Green Innovation. Green Innovation, in turn, has a significant positive effect on Sustainable Performance. However, Green Entrepreneurial Orientation does not have a significant direct effect on Sustainable Performance. The mediation analysis confirms that Green Innovation fully mediates the relationship between Green Entrepreneurial Orientation and Sustainable Performance, suggesting that entrepreneurial orientation contributes to sustainability outcomes only when translated into innovative environmental practices. These findings highlight the critical role of innovation capability in enhancing the sustainable performance of SMEs in both Indonesia and Malaysia.Conclusion: This study demonstrates that Green Innovation is a key mechanism linking Green Entrepreneurial Orientation to Sustainable Performance. The findings contribute to the Resource-Based View by emphasizing the importance of innovation capability in transforming environmental orientation into sustainable competitive advantage. Practically, the study suggests that SME managers should prioritize the development of green innovation capabilities, while policymakers should strengthen institutional support, technology transfer, and sustainability-oriented programs to foster long-term sustainable performance across SMEs in Indonesia and Malaysia.